THE ROLE OF MODERN COMPUTER TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF GYNECOLOGICAL DISEASES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This scientific article analyzes the role and significance of modern computer technologies in improving the effectiveness of treatment processes in gynecology. Technological innovations significantly enhance diagnostic accuracy, minimize invasive treatment, and accelerate the patient’s recovery process